Coerced Work under Threat of Punishment. - Hatton, Erin (University of California Press, 2020)
What do prisoner laborers, graduate students, welfare workers, and college athletes have in common? According to sociologist Erin Hatton, they are all part of a growing workforce of coerced laborers. Coerced explores this world of coerced labor through an unexpected and compelling comparison of these four groups of workers, for whom a different definition of ""employment"" reigns supreme--one where workplace protections do not apply and employers wield expansive punitive power, far beyond the ability to hire and fire. Because such arrangements are common across the economy, Hatton argues that.